Gambaran Cara Orang Tua Dalam Membentuk Kebiasan Belajar Menurut Anak - Ringga Amla (Jurnal Family Education, 2021)
This research is motivated by many teenagers who get good learning result at SLTP level Kanagarian Kinali, Kinali District, Pasaman Barat Regency. The purpose of this study is to describe the parent's way of forming the child's learning habits in terms of the following aspects: 1) arranging the learning schedule together with the child, 2) accompanying and assisting the child in learning, 3) giving praise to the child and 4) assisting the child in eliminating anxiety and saturation in learning. This study used quantitative descriptive method.The population in this study was 109 adolescents.Samples were taken 25% using stratified rondom sampling technique, so there were 27 people. collection techniques used observation and questionnaires. Technique of analysis using technique percentage. The result of this research show that parent in forming child's learning habit is included into good category